Separating fluorescent species of aqueous PbS semiconductor nanocrystals using micro-emulsions - Warner, J; Watt, A; Fernee, M; Heckenberg, N; Rubinsztein-Dunlop, H (2005)
Colloidal PbS nanocrystals over-coated with CdS are prepared in aqueous solutions and exhibit strong photoluminescence with two distinct peaks in the visible regime. A photoluminescence peak is observed at 640 nm, which is attributed to the band edge recombination in the PbS nanocrystals, and another peak at 510 nm, which is above the band edge of the PbS nanocrystals. The two PL peaks are isolated by extracting separate species of nanocrystal based upon their surface morphology. Micro-emulsions of hexane:PVA are used to remove the species containing the PL peak at 640 nm from the solution, leaving a singular peak at 510 nm. We show conclusively that the double-peaked structure observed in the photoluminescence spectra of PbS nanocrystals over-coated with CdS is due to the presence of two distinctly different nanocrystal species. © 2005 IOP Publishing Ltd.